ANALYZING THE SOCIO-POLITICAL AND ECONOMIC IMPACTS OF THE 25TH CONSTITUTIONAL AMENDMENT IN PAKISTAN: A CRITICAL STUDY - Muhammad Ibrahim; Sher Ali; Zakir Ullah; Atta Ullah (International Journal of Contemporary Issues in Social Sciences, 2024)
The merger of the Federally Administered Tribal Areas (FATA) into Khyber Pakhtunkhwa marks a pivotal move by the government of Pakistan to address longstanding law-and-order challenges and integrate the region into the national mainstream. This integration has far-reaching effects on the political, economic, and social landscape of the area. This research study examines the process of merging FATA with Khyber Pakhtunkhwa and explores the resulting socio-political and economic implications for the region. Employing a qualitative research approach, the study relies on secondary data analysis to document and analyze the key aspects of this transition. The findings suggest that this integration will pave the way for peace, prosperity, and development in the region. The merger is expected to not only enhance administrative and infrastructural development but also create new opportunities for employment, business growth, communication improvements, and positive social change.